Metodologi Kajian Ilmu Dakwah: Analisis Karya Ilmiah pada Fakultas Dakwah dan Komunikasi 1985 – 2015 - Syam, Nur (Jurnal Komunikasi Islam, 2019)
This article examines the study design and methodology applied in proselytizing science at the Faculty of Proselytizing (Da'wah) and Communication UIN Sunan Ampel Surabaya during the period 1985 to 2015. This study analysed the scientific works of the faculty academic staff and students between 1985 and 2003 through the qualitative methodology. The data collected by observation and documentation and analysed through coding, categorizing, and theming procedure. The study found that the methodology used for studying da'wah science can be categorized into five approaches: factor approach, system model or interpretive approaches or understanding the meaning of da'wah for individuals, communities or society, the developmental approach and participatory approach or Participatory Action Research (PAR).